Interaction of organizations and mass media in the actualization of social problems (on the example of the Family Inclusive Theater «i») - Sidorskaya, Iryna V. (Journal of the Belarusian State University. Journalism, 2019)
The relevance of the work is determined by the fact that modern science underestimates the role of interaction between commercial organizations and the media in solving social problems. The article examines the coverage of the project in the field of corporate social responsibility of the velcom mobile operator – the Family Inclusive Theatre «i» in the Belarusian media. The goal of the paper is to verify of the hypothesis about the importance of PR support in the realization of effective media transition. Research studies need to be studied the state of media content (the number of references, the quality of the characteristics) on the subject of this case. The subject of research are: analysis of PR support of the project, information reasons for publications, their thematic aspects and genre models. The novelty of the study is that for the first time on domestic empirical material the hypothesis about the importance of the resources of public relations for the effective media transition of the social idea has been proved. The practical significance of the paper is connected with the identification of the features of coverage of the theme of the Family Inclusive Theater «i» and the problem of autism in Belarus in the domestic mass media. This will allow us to optimize our actions both for Velcom and other organizations in the realization of social projects, as well as to increase the efficiency of journalists’ actions in solving actual problems.